2007
DOI: 10.1111/j.1558-5646.2007.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH AND SURVIVAL TRADE-OFFS AND OUTBREEDING DEPRESSION IN RAINBOW TROUT (ONCORHYNCHUS MYKISS)

Abstract: The purpose of this study was to examine, using a rainbow trout (Oncorhynchus mykiss) model system, the fitness consequences

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
97
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 58 publications
(69 reference statements)
3
97
0
Order By: Relevance
“…Transgressive phenotypes in hybrids may thus be the consequence of a deeper genetic distance between parental populations (Stelkens and Seehausen 2009). For instance, in rainbow trout (Oncorhynchus mykiss), outbreeding depression did not appear in introgressed genomes, possibly because coadapted genotypes were too similar for recombination to have a negative impact (Tymchuk et al 2007). Moreover, divergent genomes may accumulate regulatory incompatibilities resulting in occurrence of misexpressed transcripts (OD or UD) in hybrids (Landry et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Transgressive phenotypes in hybrids may thus be the consequence of a deeper genetic distance between parental populations (Stelkens and Seehausen 2009). For instance, in rainbow trout (Oncorhynchus mykiss), outbreeding depression did not appear in introgressed genomes, possibly because coadapted genotypes were too similar for recombination to have a negative impact (Tymchuk et al 2007). Moreover, divergent genomes may accumulate regulatory incompatibilities resulting in occurrence of misexpressed transcripts (OD or UD) in hybrids (Landry et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic introgression of farmed escapees into native populations (Glover et al 2012) can lead to reduced overall fitness of wild populations (Fleming et al 2000, Gilk et al 2004, Tymchuk et al 2007) and competition for food and habitat (Jonsson & Jonsson 2006, Šegvić-Bubić et al 2011a. Post-escape behaviour of coldwater-aquaculture species, such as Atlantic salmon Salmo salar or Atlantic cod, has been extensively studied (Olsen & Skilbrei 2010, Skilbrei 2010, Chittenden et al 2011, Zimmermann et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A comparison between selfing, hermaphroditic Caenorhabditis elegans and its gonochoristic (separate males and females) congeneric Caenorhabditis remanei, showed that the sexual species suffered greatly from inbreeding depression, whereas the selfing C. elegans suffered similar consequences from outbreeding (Dolgin et al 2007). In rainbow trout (Oncorhynchus mykiss) under experimental conditions, crossings between wild and captive-reared fish result in outbreeding depression ( Tymchuk et al 2007), and in natural populations of the ornate dragon lizard (Ctenophorus ornatus), more outbred females produced offspring with poorer survival (LeBas 2002). At the extreme, the risk of hybridization can potentially be an important selective pressure biasing fertilization towards genetically more similar mates.…”
Section: Introductionmentioning
confidence: 99%